The continuum of COPD: a physiological perspective - O'Donnell, Denis (Henry Stewart Talks, 2012)
Evolution of respiratory impairments from mild to sever COPD, Progression of the symptoms of COPD: dyspnea and exercise impairment, Mechanism s of progression, Optimizing respiratory mechanics